Answer:
A) -4x + 9y = 9
B) x -3y = -6
We multiply B) by 3
B) 3x -9y = -18 Then add it to A)
A) -4x + 9y = 9
-x = -9
x = 9
9 -3y = -6
3y = 15
y = 5
Step-by-step explanation:
Answer:
21
Step-by-step explanation:
Answer:
Step-by-step explanation:
a) We would use the formula for exponential growth model which is expressed as
y = b(1 + r)^t
Where
y represents the population after t years.
t represents the number of years.
b represents the initial population.
r represents rate of growth.
From the information given,
b = 5655
r = 1.4% = 1.4/100 = 0.014
Therefore, the equation would be
y = 5655(1 + 0.014)^t
y = 5655(1.014)^t
b) in 2022, t = 2022 - 2010 = 12 years
y = 5655(1.014)^12
y = 6682